FACTORS INFLUENCE THE CUSTOMER TO USE E-MONEY (CASE STUDY AT BITUNG CITY, OVO APPLICATION) - Timpua, Mitha Randa; Massie, James D. D.; Wangke, Shinta J. C. (Universitas Sam Ratulangi, 2021)
This research is to determine the factors affecting customers in Bitung city use e-money. Electronic money began to be intensified with purpose of improving cashless society toward cost and time efficiency. This study uses quantitative method using questionnaire to obtain data and use purposive sampling as sampling technique with 100 customers of OVO application. This study uses factor analysis as an analysis tool. The result indicates that there are 6 new factors formed that affecting the career development, namely: customer satisfaction, promotion, customer relationship, customer loyalty, and customer value and customer equity as respondents. Based on the result of the study, the recommendation to the company PT Visionet International (OVO) is to really consider about these factors to create efficiency and effectiveness in the marketing process in order to achieve the goals.Â Keywords: OVO application, customer decision, factor analysis